Effect of Polythene Covering on Seedling Quality and It’s Carryover Effect on Field Duration and Grain Yield of Rice - Badshah, M A; Hasan, M R; Roy, T K; Rahman, M A (Bangladesh Rice Journal, 2023)
Boro rice cultivation is often limit due to lack of a farmer's friendly technique for raising quality seedling in irrigated ecosystem. Experiment was conducted in Boro 2019-20 at R/S Rangpur to compare different polythene covering treatment on raising quality seedling of BRRI dhan88 and BRRI dhan89 and to measure it’s carryover effect on growth duration and grain yield of rice. The treatments were as T1: Day polythene cover (from10:00 am to Sunset), T2: Night polythene cover (Sunset to Sunrise), T3: Day-night polythene cover but round shape opening (30 cm diameter) at both sides and T4: No polythene cover (control). Seedbed was covered by transparent polythene from seeding to 30 days after seeding (DAS). Seedling strength was higher on 01 December seeding than 15 December in both the tested varieties. Day cover always had the lowest seedling strength in both varieties. Day-night polythene cover treatment (T3) produced significantly tallest seedling than other polythene covering treatments for both the plantings dates. Seedling mortality was higher in 30 January planting than 15 January planting for both the tested varieties due to prevailing low temperature (below 10°C for eight days). In 15 January planting, BRRI dhan88 and BRRI dhan89 produced higher number of tillers with day cover and night cover treatment, respectively. In 30 January planting, BRRI dhan88 produced higher tiller with day-night and control treatment but day cover had the lowest. Tiller production rate was sharply increased from 35 – 45 DAT and then decreased. Up to 45 DAT, it was statistically similar in both the varietiers with all treatments. Although, tiller number was higher in T1, T2 and T4 than T3 but productive tiller (%) was satistically similar among the treatments for both the varieties and planting dates. There was no significant difference in grain yield among the treatments for planting dates and varieties. Day-night polythene cover treatment (T3) reduces growth duration by 2-3 days over other treatments. This treatment (T3) is farmer's friendly for raising quality seedling in cold prone areas of Bangladesh. Bangladesh Rice J.26 (1): 59-68, 2022